Herbal Cooling Roll-On (Aloe Vera–Lavender) for the Management of Vasomotor Symptoms in Menopausal Women - Mutiara Solechah; Rissa Nuryuniarti; Sri Susilawati; Nunung Yulia (GLOBAL HEALTH SCIENCE GROUP, 2026)
Hot flashes are the most common vasomotor symptom experienced by women during the climacteric phase, often accompanied by sleep disturbances and anxiety. Hormone therapy is effective, but not all women can use it due to contraindications and the risk of long-term side effects. Therefore, non-hormonal interventions based on topical products are a potential alternative. Researcher are developing a cooling roll-on based on aloe vera, lavender hydrosol, and menthol in concentrations safe for skin application. The purpose of this study was to develop and evaluate the effectiveness of a cooling roll-on based on aloe vera, lavender hydrosol, and menthol as a non-hormonal intervention in reducing the intensity and frequency of hot flashes in menopausal women. This study used an experimental laboratory design followed by a pilot clinical trial. The initial phase involved the formulation of two cooling roll-on preparations based on aloe vera and lavender hydrosol, one with and one without added menthol. Evaluation of the preparation quality was carried out through pH testing using a calibrated pH meter and microbial contamination testing using the Total Plate Count (TPC) method. Furthermore, initial safety testing was conducted through patch tests on 10 respondents to assess potential skin irritation. Data were analyzed descriptively to assess the safety, stability, and feasibility of the product before proceeding to the clinical trial phase. The findings in this study are based on laboratory tests on coolant roll-on preparations, both with and without menthol, obtained data based on pH parameters. Preparations with menthol have an average pH of 5.91 and preparations without menthol have an average pH of 5.98. while microbial contamination (Total Plate Count/TPC) in both preparations has a TPC value <1.0 x 101 CFU/ml. Implications for Product Feasibility Based on these two parameters, it can be concluded that Initial safety is met (both formulations have met the basic criteria for topical safety, both in terms of pH and microbial contamination) and the formulation is stable (there are no significant changes due to the addition of menthol to).